Properties and characterization of banana stems / polyester resin composite - Prem Kumar A/l Gopala Krishnan (2023)
In this thesis paper, the main objective is to determine the effects of banana stem fibers on the mechanical properties and the morphology analysis of composites. Next, to apply the concept of an automotive part/ spoiler which made of economical, eco-friendly& high strength material. This study is done to develop and get a concept of a new type of car spoiler by using the mixture of powdered banana stem and polyester resin. From the usage of natural fibers banana stems as filaments to make car spoilers which are low cost, light in weight, high efficiency, reliable and longer lasting stability can be produced. Polyester resin and powdered banana stems were gotten as crude materials for the execution of this venture. The natural materials were then handled appropriately to prepare them to be required into the creation procedure. The composites were created by means of the hand lay-up technique. When the composites were prepared, they were then cut into tests for mechanical testing and morphology analysis. The mechanical testing process tensile strength, and the morphological examination includes a utilization of a filtering electron magnifying instrument (SEM). This research proves that the highest tensile strength obtained is 22.1Mpa for 10% filler loading (outer filament) and the created SEM pictures has given some proof on why the composites have lower normal rigidity properties when contrasted with past investigations of Polyester composites and the proof was the arrangement of voids in the microstructure of the composites. This happened as a result of lopsided scattering of the fibers in the grid because of the length of the banana stem/ Polyester filaments being not exactly the ideal length at 30 mm. Another factor would be that some development of minor air pockets existed during the hand lay-up technique. Subsequently, to stay away from this specific mix-up, future scientists are encouraged to use infusion forming rather to maintain a strategic distance from conceivable human mistakes during the creation method. From the results, can conclude that, for tensile purposes, this thesis suggests an outer filler loading of either 10 % or 20 % for an optimum material performance, although future researchers can try to investigate an optimal balance between the two values of volume fractions.